Facile synthesis of biocompatible N, S-doped carbon dots for cell imaging and ion detecting. Issue 21 (6th March 2015) - Sun, Yupeng; Shen, Chen; Wang, Jing; Lu, Yun
<x xml:space="preserve">Abstract</x> A facile, simple, effective and green method has been developed to synthesize nitrogen and sulfur co-doped carbon dots (N, S-CDs) from heparin sodium.